State of peroxidation processes in pregnant women with somatoform dysfunction of vegetative nervous system - Syusyuka, V. G. (Pathologia, 2014)
Extragenital pathology of pregnant women continues to be one of the main reasons of the serious complications of gestation which promotes increase of maternal and prenatal disease incidence. In accordance with International Classification of Diseases-10 neurocirculatory dystonia (NCD) refers to the section “Somatoform vegetative dysfunction of heart and cardiovascular system”. Today a relationship between peroxidation intensity and severity level of the disease is proved and important role of the emotional stress in the development of NCD is determined. Object of the work – to estimate oxidative modification of proteins and antioxidative system of protection of the pregnant women with neurocirculatory dystonia. Group of examined persons and methods of investigations The main group consisted of 43 pregnant women with somatoform dysfunction of vegetative nervous system (SDVNS) and 32 somatically healthy pregnant women who were improving their health and getting rehabilitation in a special department for pregnant women in sanatorium “Velikiy Lug”. Level of trait anxiety (TA) and state anxiety (SA) was objectified by means of technique of Ch. D. Spielberg which had been adapted by Yu. L. Hanin. Investigations of markers of oxidative modification of proteins (OMP) were estimated in the blood serum with spectrophotometric method when length of the wave was 270nm (aliphatic aldehyde dinitrophenylhydrazones –APH) and 363 nm (carbonyl dinitrophenylhydrazones – CPH). State of antioxidative system of protection was determined in accord with level of activity of superoxide dismutase (SOD). Results of investigations and their discussion Investigation of parameters of oxidative modification of proteins in groups under research permits to determine the highest content of spontaneous APH definitely, that the pregnant women with SDVNS have in comparison with women of control group (p<0.05). During estimation of metal-catalyzed oxidation of proteins the highest level of both APH and CPH that women with SDVNS have in comparison with the correspondent index of the control group (p<0.01) was determined. During estimation of antioxidative system of protection the highest level of SOD of 9.39±0.6 c.u./mg/protein/min, that the pregnant women of the control group have, comparing to the correspondent index of 6.07±0.5 c.u./mg/protein/min., that the pregnant women of the main group have, was definitely determined (p<0.1). Conclusions 1. On the basis of the investigation carried out high percentage of the pregnant women with medium and high levels of the trait and state anxiety both among women with somatoform dysfunction of vegetative nervous system and somatically healthy pregnant women was determined. 2. Connection between markers of spontaneous and metal-catalyzed OMP and trait anxiety both in the main group (r=+0.7 and r=+0.6 correspondently) and in the control group (r=+0.5 and r=+0.6 correspondently) was determined. 3. Investigations of parameters of oxidative modification of proteins permitted to determine definitely the highest level of spontaneous OMP (APH) and absence of evident difference between content of spontaneous OMP (CPH) in case of the pregnant women with SDVNS comparing to women of the control group. 4. Determined evident highest level of stimulated OMP both as APH and CPH, that the pregnant women with SDVNS have, in comparison with the correspondent index of the control group (p<0.01) shows significant changes in regulation of oxidative-antioxidative homeostasis associated with the disorder of antioxidative protection. 5. Enhancement of oxidative processes in case of lack of antioxidative protection system leads to development of oxidative stress and is one of the mechanisms of complicated course of gestation of the pregnant women with SDVNS.